近隣苦情・相談において保健師が困難ケースと認識した精神障害者の特徴 - 吉岡 京子; 黒田 眞理子; 蔭山 正子 (日本公衆衛生看護学会誌, 2017)
Objectives: The purpose of this study was to clarify the characteristics of mentally ill persons who are identified as being difficult cases by public health nurses as a result of neighbors’ complaints, and who eventually receive psychiatric treatment.Methods: We analyzed the results of anonymous self-administered mail survey questionnaires that were answered by 261 public health nurses who were in charge of mental health care in 53 municipalities (valid response rate: 39.6%). The cases were divided into 2 groups based on the mentally ill person received psychiatric treatment as a result of the neighbors’ complaints or not. We conducted logistic regression analysis to investigate related factors for receiving psychiatric treatment as a result of neighbors’ complaints.Results: Among the 261 persons, 156 received psychiatric treatment as a result of neighbors’ complaints (59.8%). Logistic regression analysis demonstrated that mentally ill persons who were male (odds ratio [OR]=0.33, 95% confidence interval [CI]=0.13–0.81), whose family assisted in visiting a psychiatric hospital (OR=10.14, 95%CI=2.67–38.51), who have an unsanitary appearance (OR=6.99, 95%CI=1.59–30.79), and having a fear of self-injury (OR=6.06, 95%CI=1.33–27.61) were more likely to receive psychiatric treatment as a result of neighbors’ complaints.Conclusion: Our results indicated that mentally ill persons with lower self-care levels were more likely to receive psychiatric treatment as a result of the neighbors’ complaints, via the support of public health nurses. 目的：近隣住民等からの苦情・相談（近隣苦情・相談）で保健師が困難ケースと認識した精神障害者と，それを契機に医療につながった者の特徴を解明する．方法：全国53自治体の精神保健担当保健師261人に無記名自記式郵送調査を行い（有効回答率39.6%），ロジスティック回帰分析を行った．結果：医療につながった者は156人（59.8%）で，医療につながったことに有意な関連が見られたのは，属性では男性であること，家族要因では精神科医療機関受診時に親族の協力が得られたこと，精神科要因では不潔な身なりと自傷のおそれがあることであった．結論：精神障害者のセルフケア能力の低下への着目は，早期受診の一助になると考えられる．